Image Schema Analysis on Psalm 23: A Study of Metaphor Based on Cognitive Theory - Subianto, Paulus (e-Journal of Linguistics, 2019)
This article aims to identify what types of image schemas operating in Psalm 23 “The Lord is My Shepherd. This text is very old and full with metaphors. According to the theory of Conceptual Metaphor, metaphorical phenomena are not merely as a linguistic matter, but rather as a process of cognition by which humans understand the reality (Lakoff and Johnson,1980). Unconsciously, conceptual metaphor generates metaphorical expressions in our daily life. Behind the conceptual metaphor, there are image schemas serving as a pre-conceptual structure derived from physical experiences, cultural background, and ideology of a nation. Image-schema is a recurring structure within our cognitive process (Johnson,1987).  The Psalm 23 “The Lord is my Shepherd” consists of 6 verses, each may be contained of more than one sentence or phrase. It was written by King David about the fifth and the tenth century B.C. to show the goodness of God, and His close relationship with His people. God is portrayed as a good shepherd caring deeply to His cattle. Mapping method is adopted to construct the meaning of metaphor in which The Lord as Target Domain and Shepherd as Source Domain. Then, each verse is analyzed to find image schemas involved in the text. As the result, there are seven types of image schemas in Psalm 23: container, path, link, force, attraction, blockage, and removal of restraints. Based on these findings, it can be concluded that image schema as an elementary part of conceptual metaphor has potential to be an analysis tool to discover the meaning of metaphorical texts.